Mewujudkan kesejahteraan bersama: Konsep distribusi dalam ekonomi Islam - Ridwanillah, Ach. Nailu; Yunus, Muh. (Maliki Interdisciplinary Journal, 2025)
This discussion explores the concept of distribution in Islamic economics, which emphasises justice, equity and collective welfare as the basis of social welfare. Unlike conventional economics, which focuses on the accumulation of wealth through market mechanisms, Islamic economics introduces mechanisms such as zakat, infaq, sadaqah and waqf to prevent the accumulation of wealth in the hands of a few. This research was conducted through a literature review method by analysing relevant literature from various local and international sources. The principles of distributive justice and honesty in Islamic economics, including the prohibition of usury and the importance of business ethics, are of primary concern. In addition, the distribution of wealth in Islam is not only economic but also moral and spiritual, creating economic independence and strengthening the social fabric of society. The challenges of applying these principles in the modern world, particularly in relation to economic inequality, are also discussed. The main objective of distribution in Islam is to achieve Maqashid Shariah, which prioritises social welfare and economic stability. Through the use of Islamic economic tools, this research offers a new perspective on the challenges of today's global economy.